Innovation Utilization of Tofu Waste Into Flour With The Addition of Sodium Metabisulfit As Antibrowning - Nailul Hidayat; Rita Sunartaty; Salfauqi Nurman; Irmayanti Irmayanti; Sholihati Sholihati (Serambi Journal of Agricultural Technology, 2019)
Tofu waste has a high nutritional value because in the manufacturing process, not all protein content can be extracted. At present the use of tofu waste is used as a manufacture of gusts, crackers, soy sauce and animal feed. Even though 100 grams of tofu waste still has a carbohydrate content of 11.07%, 4.71% protein, 1.94% fat and 0.8% ash. Tofu waste can be processed into flour by passing the bleaching process using sodium metabisulfite. The purpose of this study is to find out the making the flour  from tofu waste using sodium metabisulfite as anti browning. This research was carried out using factorial Randomized Complete Design (RAL) with variations in the concentration of sodium metabisulfite namely 0, 100,300 and 500 ppm and immersion duration of 30, 45, and 60 minutes. In this study, the best treatment was produced by soaking sodium p-metulfulfite 500 ppm with 60 minutes immersion time producing tofu flour with moisture content 9.43%, ash content 2.17%, organoleptic test aroma 3.87 (likes) color (4, 03) like it.